Kritikan sosiobudaya dalam filem seram (horror) Melayu terkini / Che Nurulizatie Che Mazlan - Che Mazlan, Che Nurulizatie (Faculty of Film, Theatre and Animation, 2012)
This dissertation is made in order to analyze the socio-cultural critism in Malay Horror Films. Findings from this study cover two main objectives , namely to identify social-cultural critique found in horror films and interpretation of socio-cultural elements in a horror film. This research will use Pontianak Harum Sundal Malam (2004), Susuk (2008) and Hantu Kak Limah Balik Rumah (2010) as guidance. Qualitative methods were used in this study to obtain sources of information using educational materials covering books, journals, magazines and articels from World Wide Web. This research not only to understand and interpret the film, but to understand the culture of the Malay community is practiced and handed down from the past to present.